IZZY : a biography of i. f. stone. - COTTRELL, ROBERT C. (RUTGERS University Press, 2020)
This is the classic story of the life and times of I. F. "Izzy" Stone. Robert Cottrell weaves together material from interviews, letters, archival materials, and government documents, and Stone's own writings to tell the tale of one of the most significant journalists, intellectuals, and political mavericks of the twentieth century. The story of I. F. Stone is the tale of the American left over the course of his lifetime, of liberal and radical ideals which carried such weight throughout the twentieth century, and of journalism of the politically committed variety. Now available in a handsome new Rutgers University Press Classic edition, it is an examination of the life and career of a gregarious yet frequently grumpy loner who became his nation's foremost radical commentator provides a window through which to examine American radicalism, left-wing journalism, and the evolution of key strands of Western intellectual thought in the twentieth century.